Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Listrik Kabupaten Manokwari (Studi Kasus Kelurahan Amban) - Suryani Goga; Lillyani M. Orisu; Marcus R. Maspaitella (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2020)
Purpose of this study was to analyze the effect of the number of electronic furniture, the number of lamps, the number of family dependents, income and electrical power on the electricity demand by households in Amban Village, Manokwari Regency. The data obtained comes from the results of interviews and literature review that supports this research. The analytical tool used in this research is multiple linear regression. The results showed that the number of electrical furniture, the number of lamps and the number of dependents did not affect household electricity consumption, while income and electrical power did not affect household electricity consumption demand.